Noise-optimized virtual monoenergetic reconstructions of dual-energy CT angiographies improve assessability of the lower leg arterial segments in peripheral arterial occlusive disease. Issue 1 (January 2023) - Gruschwitz, P.; Petritsch, B.; Schmid, A.; Schmidt, A.M.A.; Grunz, J.-P.; Kuhl, P.J.; Heidenreich, J.F.; Huflage, H.; Bley, T.A.; Kosmala, A.
Abstract: Introduction: The aim of this study was to evaluate the influence of a noise optimized virtual monoenergetic reconstruction algorithm (VMI+) on the image quality and assessability of dual energy (DE) computed tomography angiography (CTA) of the lower extremity runoff. Methods: A total of 118 lower extremity runoff CTA performed on a 3rd generation DE-CT scanner in 109 patients (54 females; 75.6 ± 9.5 years) were included in this retrospective study. Axial image stacks were reconstructed with a standard 120 kV setting and VMI+ of different keV levels. Objective image quality criteria (contrast attenuation, signal-to-noise [SNR] and contrast-to-noise ratio [CNR]) were measured. Two radiologists evaluated subjective image quality regarding intraluminal attenuation and image noise using a 5-point Likert scale. Diagnostic accuracy for significant stenosis (>75%) and vessel occlusion was assessed for 120 kV and 50 keV VMI+ images rated by two radiologists. In all patients, a digital subtraction angiography (DSA) rated by on board-certified radiologist served as the standard of reference. Results: Intraluminal attenuation was highest in 40/50 keV VMI+ while SNR were similar to 120 kV images. In subjective assessment, intraluminal contrast of 50 keV images was deemed superior compared to 120 kV despite higher image noise. Sensitivity, specificity, and accuracy for detection of a vessel occlusion were similar in 50 keV VMI+ compared to 120 kV (70%/92%/84%; 70%/91%/83%; p < 0.001) but 13 of 118 (11%) lower leg runoffs were only assessable with 50 keV VMI+. Conclusion: VMI+ reconstructions improve assessability of DE-CTA by increased luminal attenuation with consistent image noise, also allowing the evaluation of lower leg arterial segments inassessable with standard reconstructions. Implications for practice: Providing higher intraluminal attenuation and similar image noise compared with conventional reconstructions, 50 keV VMI+ may be appropriate for routine evaluation of DE-CTA.